Comparison of reflux characteristics between grade A and grades B/C reflux esophagitis based on esophageal pH-impedance monitoring - Sihui LIN; Zhilong CHEN; Yucheng ZHU; Wei JIANG; Dalong SUN (Zhongguo Linchuang Yixue)
ObjectiveTo compare the reflux characteristics between reflux esophagitis (RE) patients with Los Angeles (LA) classification grade A and grades B/C based on esophageal pH-impedance monitoring results. MethodsA total of 74 RE patients at Zhongshan Hospital (Xiamen Branch), Fudan University from June 2021 to June 2024 were enrolled, and were divided into the LA-A group (n＝46) and the LA-B/C group (n＝28) based on the endoscopic diagnosis results. The general clinical data, symptom questionnaire score, and esophageal 24-hour pH-impedance monitoring results were compared between the two groups. ResultsThere were no statistically significant differences in demographic data and the response rate of acid suppression therapy between the two groups. 24-hour esophageal pH-impedance monitoring results showed that there were no statistically significant differences in upright, supine, and total reflux indices, including reflux episodes, acid exposure time (AET), AET percentage (AET%), long acid reflux episodes, longest reflux duration, and total DeMeester score between the two groups. There were no statistically significant differences in distal reflux episodes, proximal reflux episodes, and high reflux (acid, weak acid, and non-acidic reflux) episodes, mean nocturnal baseline impedance (MNBI) between the two groups. The rates of pathological reflux (AET%≥6%) in LA-A group and LA-B/C group were 67.4% and 71.4%, respectively; there were no statistically significant differences in the ratio of AET% composition and the count of impedance reflux exceeding 80 during 24 h between the two groups.ConclusionsLA-A grade RE based on the endoscopic diagnosis facilitates the identification of gastroesophageal reflux disease in the Chinese population